2009
DOI: 10.1097/bsd.0b013e31818a38cd
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reliability of 3 Thoracolumbar Fracture Classification Systems

Abstract: As a management tool, the TLISS seems to be an acceptably reliable system when compared with the Denis and AO systems. There is a base level of knowledge and familiarity necessary for the application of the system at reliable levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 7 publications
2
21
0
1
Order By: Relevance
“…This decreased to 0.48 in the radiologists subgroup, although 1 musculoskeletal radiologist obtained the best agreement. These data coincide with those obtained by Lenarz et al, 15 who demonstrated greater interobserver reliability with CT among the spinal surgeon group (kappa50.71) compared with the nonspinal surgeon group (kappa50.52). This difference may be due to the fact that surgery offers the possibility of learning to recognize fracture patterns on imaging modalities along with the experience of direct contact with its real morphology.…”
Section: Discussionsupporting
confidence: 90%
“…This decreased to 0.48 in the radiologists subgroup, although 1 musculoskeletal radiologist obtained the best agreement. These data coincide with those obtained by Lenarz et al, 15 who demonstrated greater interobserver reliability with CT among the spinal surgeon group (kappa50.71) compared with the nonspinal surgeon group (kappa50.52). This difference may be due to the fact that surgery offers the possibility of learning to recognize fracture patterns on imaging modalities along with the experience of direct contact with its real morphology.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Lenarz et al 32 was on the objective to compare and evaluate the reliability of the Denis, AO and TLISS classification systems. They concluded that the highest reliability was for the attending and senior resident group (kappa = 0.71, 0.79, 0.70) and the lowest for the junior resident and non-spine-attending surgeon group (kappa = 0.52, 0.52, 0.45).…”
Section: Discussionmentioning
confidence: 99%
“…12 Several classifications have appeared over time regarding spinal fractures, aimed at defining their level of deformity, stability and neurological risk, 13 according to vertebral morphology, the integrity of soft tissues, especially of the posterior ligamentous complex, 14 or the neurological risk. The references contain a great many articles which assess these classifications using correlation, concordance or reproducibility 15,16,12,17 and they usually conclude that there is a need for additional studies to prove the superiority of one of these classifications over the others. 18---20 For the diagnosis of patients with spinal column trauma with suspicion of severity, CT is the method of choice to assess the degree of vertebral collapse and measure the diameter of the spinal canal.…”
Section: Discussionmentioning
confidence: 99%